Implementation of Trajectory Dribbling Exercises to Improve Soccer Playing Skills - Burhanudin, Mohamad; Permadi, Asep Angga; Kurniawati, Ani (Jurnal Porkes, 2024)
Every soccer player must have basic technical skills in the game of football, one of which is the dribbling technique. So in dribbling the ball a soccer player needs good and varied training so that the results obtained will be achieved optimally, dribbling also depends on the ability of the body's movement system to respond to the situations and conditions faced and desired. This study aims to find out whether there is an effect of implementing dribbling trajectory exercises to improve soccer playing skills. The method used is an experiment with a one group pretest-posttest design. This research was conducted at Miftahul Hidaya Middle School Plus, Garut Regency with a population of 22 students. The test instrument used is a test of basic dribbling technique skills in soccer games. Data management used SPSS version 26. From the results of the data above it can be concluded that there is a significant effect of the dribbling trajectory training program on improving players' playing skills when given an average pre-test and post-test. a score of 0.3909 competes. It is known that the sig(2-tailed) value is 0.000 <0.05, so it can be concluded that there is a significant difference in the results of the trajectory dribbling exercise on the pretest and posttest data.